Liturgi Yang Sempurna Berpartisipasi Dalam Kehidupan: Tinjauan Kritis atas Praktik Berliturgi di Gereja dari Perspektif Trinitas - Hizkia Anugrah Gunawan (STFT Jakarta, Indonesia, 2018)
In the church, perfect liturgy is understood as worship’s condition without disruption or mistake. In reality, this perspective often makes some opportunity to discriminate some people from the worship. Research about liturgy, both from theologians, liturgy workers, and scripture text, indicates that the “real” perfect liturgy happens when people participate in daily life. This notion is same as the spirituality of Trinity. This spirituality explains that participation is the form of completeness or perfect God. Therefore, Trinitarian liturgy should show perfect liturgy as active participation from all people in their daily life so that can bring a goodness for others people. Key Words: worship, liturgy, perfect, Trinity, participation, church, daily life.